Implementasi Algoritma K-Medoids dan Aplikasi RapidMiner dalam Pengelompokkan Kasus BALITA Stunting - Sari, Dian Permata (LPPM STIKOM Tunas Bangsa, 2023)
Stunting is a condition where a child's growth is disrupted, one of which is characterized by the child's growth being abnormally tall, so that it is lower than children his age. Genetic factors have a very small influence on stunting cases compared to environmental factors and health services. In the Tarab River area itself, the biggest factors causing stunting in children are poor nutrition, economics and latrines. In this study the author tried to group stunting cases in the Sungai Tarab II community health center using the k-medoids method, the variables used were age, economic status, latrine conditions and complete or incomplete immunization. The results of research using the k-medoids method which carried out manual calculations obtained 2 clusters, namely cluster 1 and cluster 2 and the results could be obtained in iteration 1 where the difference was 1.112854. As for cluster 1, children are categorized as not being in the stunting category, while cluster 2 children are categorized as stunting.